The Role of Resting-State Network Functional Connectivity in Cognitive Aging - Hausman, Hanna K.; O’Shea, Andrew; Kraft, Jessica N.; Boutzoukas, Emanuel M.; Evangelista, Nicole D.; Van Etten, Emily J.; Bharadwaj, Pradyumna K.; Smith, Samantha G.; Porges, Eric; Hishaw, Georg A.; Wu, Samuel; DeKosky, Steven; et al. (Frontiers in Aging Neuroscience, 2020)
Aging is associated with disruptions in the resting-state functional architecture of the brain. Previous studies have primarily focused on age-related declines in the default mode network and its implications in Alzheimer’s disease. However, due to mixed findings, it is unclear if changes in resting-state network functional connectivity are linked to cognitive decline in healthy older adults. In the present study, we evaluated the influence of intra-network coherence for four higher-order cognitive resting-state networks on a sensitive measure of cognitive aging (i.e., NIH Toolbox Fluid Cognition Battery) in 154 healthy older adults with a mean age of 71 and education ranging between 12 to 21 years (mean=16). Only coherence within the cingulo-opercular network (CON) was significantly related to Fluid Cognition Composite scores, explaining more variance in scores than age and education. Furthermore, we mapped CON connectivity onto fluid cognitive subdomains that typically decline in advanced age. Greater CON connectivity was associated with better performance on episodic memory, attention, and executive function tasks. Overall, the present study provides evidence to propose CON coherence as a potential novel neural marker for nonpathological cognitive aging.